Peace Corps Volunteers: Culture Shocks Encountered and Strategies to Overcome During Pre-Service Training in Indonesia - Fathor Rasyid (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2021)
The purpose of the study is to examine the multifaceted reality of culture shocks experienced by Peace Corps Volunteers (PCV) during Pre-Service Training (PST) in Kediri, Indonesia and the strategies to overcome on a day to day basis. The research is descriptive in nature by semi-structured interviews and direct observation to PCV living in Kediri. The results of the research reveal that the culture shocks encountered are of three sorts: psychological, behavioral, and interpersonal communication change. Psychological change is of four kinds: using right-left hand, male-female interaction, asking personal privacy, and shake-hand. Moreover, the study also reveals three strategies to cope with culture shocks. They are self-confidence and optimism, accepting a new culture, and social support. It may be difficult to PCV to accept all differences with pleasure. However, a tolerant attitude and an open mind make them better to communicate with Community Liaison (CL). Eventually, by other people’s assistance, the PCV were able to encounter the culture shock.